Ethanol steam reforming over calcium doped Ni/Al2O3 catalyst - Azizan, M.T. (Trans Tech Publications Ltd, 2014)
Steam reforming of ethanol has been carried out using a commercial catalyst (Hi-FUEL) of calcium doped nickel/alumina catalyst. Hi-FUEL had successfully reformed ethanol into the desired products at relatively high yield and selectivity. The hydrogen yield of 90.5 has been achieved from this catalyst with almost no ethylene detected. Hi-FUEL is also comparable with other calcium doped nickel/alumina catalyst as reported by other researchers. Â© 2014 Trans Tech Publications, Switzerland.